2013
DOI: 10.3354/dao02562
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting variation in mortality of marine Atlantic salmon Salmo salar in Scotland

Abstract: Databases of site production have an important role to play in the investigation and understanding of diseases, since they store valuable amounts of disease and management data. Diseases pose an important constraint to economic expansion of aquaculture. They are dependent on the complex interacting factors of pathogen, environment, and host, and the causes of death can be related to nutritional, environmental, and genetic factors of the host or infectious agents. We examined the drivers of mortality from a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Considering that the present study resulted from a chance finding during the course of a myxozoan survey conducted on Archosargus probatocephalus (work in progress), we are unable to say whether the RLOs described here can increase host mortality. Nevertheless, a previous study showed that infection by RLOs may occur through weakened host immunity, as a result of abiotic changes to the aquatic environment (Soares et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the present study resulted from a chance finding during the course of a myxozoan survey conducted on Archosargus probatocephalus (work in progress), we are unable to say whether the RLOs described here can increase host mortality. Nevertheless, a previous study showed that infection by RLOs may occur through weakened host immunity, as a result of abiotic changes to the aquatic environment (Soares et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These are commonly associated with differing pathogenicity in many geographical regions (Athanassopoulou & Karagouni, 2004;Azevedo, 1993;Azevedo et al, 2005;Birkbecka & Ringøb, 2005;Bower et al, 1994;Cusack et al, 2002;Fryer et al, 1990;Fryer & Lannan, 1994;Guo et al, 2004;Molloy et al, 2001;Turnbull, 1993;Villalba et al, 1999;Yuksel et al, 2006). Rickettsial and bacterial diseases that affect a wide range of freshwater, brackish water and marine fish (Bower et al, 1994;Mauel et al, 2003;Soares et al, 2013;Weinert et al, 2009), including ornamental species (Mauel et al, 2007) have been described. Elevated economic losses due to occurrences of rickettsial infections in cultivated fish have also frequently been reported (Branson & Diaz-Munoz, 1991;Chern & Chao, 1994;Corbeil et al, 2005;Cusack et al, 2002;Fryer et al, 1990;Mauel et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Water temperature may also affect salmon health and its capacity to cope with stressors. For example, Soares et al (Soares et al, 2013) found that cohorts of smolts transferred to the marine environment in the third quarter of the year, when water temperatures are increasing, showed the highest mortality. Stene et al (2014a) observed that cohorts of salmon that become infected when the sea temperature decreases have longer incubation periods and may therefore sere longer as asymptomatic reservoir than when the water temperature is increasing.…”
Section: Changing Weathermentioning
confidence: 99%
“…Prevention is a key element in the control of disease establishment. Early and precise diagnosis, effective prevention measures and accurate epidemiological surveys are essential for minimizing the impact of infectious and non-infectious diseases in fish culture (Soares et al, 2013). The viral infectious salmon anaemia (ISA) and pancreatic disease (PD) together with salmon sea lice are considered to be the main health management issues in Atlantic salmon farming.…”
Section: Control Measures For Farmingmentioning
confidence: 99%